SISTEM APLIKASI CUTI KARYAWAN BERBASIS WEB PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU SATU PINTU KOTA MEDAN - Sinaga, Yulia Alfi; Aida, Maghfira (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2025)
Agencies must effectively manage employee leave management as one of their important responsibilities. Currently, many agencies, including the Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Medan, still use manual methods in handling employee leave applications, namely by manually creating leave letters using templates and submitting them to the Head of the Personnel Sub-Division for approval. This manual process is time-consuming, prone to errors, and makes it difficult to manage leave data. To overcome this problem, a web-based employee-leave application system at DPMPTSP Medan uses the PHP programming language and MySQL database. The design of this website involves several stages, including interviews, data collection, observation, and data analysis. The design of the employee leave website is then carried out by analyzing and designing each component using UML. This system is designed to simplify the leave application process, provide easier access to employees, and minimize administrative errors. The results of this study indicate that the developed system has succeeded in increasing the efficiency of the leave application process. Functional and security tests conducted showed that the application functions according to specifications and is able to maintain data integrity. This system makes it easier for employees to apply for leave because it can be done anywhere and allows the personnel department to verify and approve applications more quickly and accurately.